Renewable Energy Engineering: Solar, Wind, Biomass, Hydrogen and Geothermal Energy Systems - D. Rogdakis, Emmanuel; P. Koronaki, Irene (Bentham Science Publishers, 2018)
Researchers, politicians and lay persons around the world agree that renewable energy technologies will play an increasingly important role in strengthening national economies in the future. The renewable energy industry has the potential to significantly increase power capacity of several countries and subsequently create many jobs.This book examines recent advances in specific renewable energy systems. Readers will learn about theoretical and applied perspectives which are key to addressing the major issues associated with such systems. Chapters cover solar energy systems, thermal energy storage, bioenergy, hydrogen production, geothermal energy and measurement techniques for these energy systems. Students in engineering programs, and engineers working in academia and the renewable energy sector will be able to broaden their understanding of complex renewable energy projects through the comprehensive overview of both the fundamental concepts and the technical issues covered in the text.